Efecto de la permanencia de un dispositivo intravaginal con progesterona sobre la eficiencia reproductiva de vaquillonas Holando - Callejas, S. (2008)
The objective of the present work was to evaluate the effect of the presence of progesterone (0.558 g) intravaginal devices for 7 or 8 days on reproductive efficiency. A total of 53 Holstein heifers (20-27 month-old; 3.9±0.2 body condition score) were used. Heifers were assigned to 2 treatment: 1) M24 7d: Day 0, insertion of intravaginal device (0,558 g progesterone) + 2 4 7d: mg of estradiol benzoate (EB); day 7, device removal and administration of 150 mg of DCloprostenol; day 8, 1 mg EB; day 9, (Fixed Timed Artificial Insemination (FTAI); 2) M24 8d: Similar to M24 7d, but the permanence of the device was of 8 days. Seventeen to 25 days after FTAI, heifers returning to estrus were inseminated. Pregnancy diagnosis was done by ultrasonography 28 days after FTAI (FTAI pregnancy) and by transrectal palpation at 60 day after return to estrus (estrus return pregnancy). There was no effect of treatments on pregnancy rate at FTAI (63.0 vs. 73.1%), pregnancy rate to detected heat (57.1 vs. 50.0%), general pregnancy rate (77.8 vs. 84.6%), and heat detection rate (70.0 vs. 85.7%) (P>0.05). In conclusion, the device with 0.558 g of progesterone can remain in the vagina for 7 or 8 days without affecting reproductive efficiency of Holstein heifers.